PERTANGGUNGJAWABAN PIDANA ADVOKAT PADA OBSTRUCTION OF JUSTICE DALAM PERKARA TINDAK PIDANA KORUPSI - Bijayanti, Kadek Indah; Darmadi, AA Ngurah Oka Yudistira (Kertha Wicara : Journal Ilmu Hukum; Vol 9 No 4 (2020), 2020)
As a part of Indonesian Criminal Law No 20 of 2001 which concern about Eradication of Corruption , obstruction of become part of corruption is examined to threaten the advocate profession in protecting the interests of clients. Advocates have the imunnity right to form of protection for their profession which makes an advocate unable to be prosecuted criminal or civil during their duties and profession in Law Number 18 Year 2003 concerning Advocates. This research have an aim to know legal aspect of advocate in law enforcement obstruction of justice , also to find out the criminal responsibility of advocate in obstruction of justice that they do in the process of law enforcement for criminal action .This research using doctrinal methods. The results showed that the right to immunity applies as far as its bad that must be fulfilled by advocates both outside and inside the trial in order to protect the legal concerns of the client.Although the criminal liability of lawyers in obstruction of justice when it is proven to be harmful by conducting unlawful acts to obstruct the process of law enforcement of coruption, it possible to be held professionally and criminal liability.